PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 01 TALANG MANDI KECAMATAN MANDAU KABUPATEN BENGKALIS - Guswanti, Guswanti; Lazim N, Lazim N; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak : This research was conducted because of the result of learning IPA class IVA SD Negeri 54 Sebangar. From 25 student who achieve KKM just 10 student (38,46%) while student who did’nt complete 15 student (61,54 %) with an average of 60.This aims of study to increased study result IPS school years 2015-2016. This subjet research of this study are the study are the students of class IV SDN 01 Talang Mandi Kecamatan Mandau kabupaten Bengkalis. This research are action research class with two cycle. This case can prove with the score activity teacher can get from each appointment increased progress. One cycle from first appointment teacher activity presentation are 75% with the goodcategory and second appointment are 87,5% with the good category. Cycle 2 first appointment increased to 85% with the excellent category and the second appointment increased again to 90% with the excellen category. While the activity students first cycle on the first appointment can get 60% with the good category and the second appointment inceased to 65% with the good category, two cycle on the first appointment increased again to 75% with the excellent category and the second appointment increased again to 87,5% with the excellent category. This aims of this study can experience increased to from basic score can reach average 58,33 appointment 18,46% to daily exam I 74,96 and can increase to daily exam II to 37,1% average 80 . Therefoe can conculeded that hypothesis in this research are if the applied learning cooperative type NHT an increase the stdies result IPS class IV SDN 01 Talang mandi Kecamatan Mandau Kabupaten Bengkalis.Keywords : Numbered Head Together, Learning Outcomes IPS